2009
DOI: 10.1002/pbc.21992
|View full text |Cite
|
Sign up to set email alerts
|

Progressive neurocognitive impairment in young adult survivors of childhood acute lymphoblastic leukemia

Abstract: Survivors of childhood ALL suffer from long-lasting progressive neuropsychological impairment, especially when treatment includes cranial irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 43 publications
1
77
0
1
Order By: Relevance
“…Of the 42 studies, 13 were excluded because patients were less than 5 years since diagnosis or 2 years since the end of treatment, 8 because they lacked a healthy control group, 6 because some/all patients received cranial radiation, and 5 because they did not directly assess neurocognitive outcomes of interest (summarized in Figure 1). Ten studies 11,19,[26][27][28][29][30][31][32][33][34] remained that met all the predefined inclusion criteria (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 42 studies, 13 were excluded because patients were less than 5 years since diagnosis or 2 years since the end of treatment, 8 because they lacked a healthy control group, 6 because some/all patients received cranial radiation, and 5 because they did not directly assess neurocognitive outcomes of interest (summarized in Figure 1). Ten studies 11,19,[26][27][28][29][30][31][32][33][34] remained that met all the predefined inclusion criteria (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies evaluated verbal memory, the ability to encode and retrieve verbally presented information, 11,27,28,30 Only 2 of the studies found diminished verbal memory functioning in the ALL survivor group compared with the healthy control group.…”
Section: Verbal and Visual Memorymentioning
confidence: 99%
See 2 more Smart Citations
“…There is a clear role for emergent cranial radiation therapy in moribund patients with bulky CNS disease at presentation (Cuvelier et al, 2008). However cranial radiation therapy for childhood ALL is associated with an increased risk of neurocognitive deficits, particularly in younger children, which may be progressive (Spiegler et al, 2006;Harila et al, 2009). There is recent data supporting the use of dasatinib for Ph+ CNS disease (Porkka et al, 2008), and the introduction of dasatinib and intensive induction therapy led to rapid regression of bulky intracranial disease and steady neurological recovery in both cases.…”
mentioning
confidence: 99%